An intermetallic powder-in-tube approach to increased flux-pinning in Nb3Sn by internal oxidation of Zr. (28th November 2017) - Motowidlo, L R; Lee, P J; Tarantini, C; Balachandran, S; Ghosh, A K; Larbalestier, D C
Abstract: We report on the development of multifilamentary Nb3 Sn superconductors by a versatile powder-in-tube technique (PIT) that demonstrates a simple pathway to a strand with a higher density of flux-pinning sites that has the potential to increase critical current density beyond present levels. The approach uses internal oxidation of Zr-alloyed Nb tubes to produce Zr oxide particles within the Nb3 Sn layer that act as a dispersion of artificial pinning centres (APCs). In this design, SnO2 powder is mixed with Cu5 Sn4 powder within the PIT core that supplies the Sn for the A15 reaction with Nb1Zr filament tubes. Initial results show an average grain size of ∼38 nm in the A15 layer, compared to the 90–130 nm of typical APC-free high- J c strands made by conventional PIT or Internal Sn processing. There is a shift in the peak of the pinning force curve from H / H irr of ∼0.2 to ∼0.3 and the pinning force curves can be deconvoluted into grain boundary and point-pinning components, the point-pinning contribution dominating for the APC Nb-1wt%Zr strands.